(untitled) (Journal of Mathematical Study, 2017)
We study the growth of solutions of higher order complex linear differential equations in an angular domain of the unit disc instead of the whole unit disc. Some estimations of [p,q]-order of solutions of the higher order differential equations in an angular domain are found in this paper.